ANALYSIS OF THE FACTORS AFFECTING THE LEAD TIME FOR EXPORT OF READYMADE APPARELS FROM BANGLADESH; PROPOSALS FOR STRATEGIC REDUCTION OF LEAD TIME - Shahidul Kader; Maeen Md. Khairul Akter (European Scientific Journal, ESJ, 2014)
A lead time is the latency between the initiation and execution of a process. In apparel industry, lead time is the total amount of time required for completing a product beginning from the date of receiving the order to the shipment of the goods to customer. Time is a great issue in apparel trade as orders are based on weather, seasons and occasions. Lead time hence, carries huge importance when delivering the products to the respective outlets is concerned. Bangladesh, though the second largest exporter of readymade apparel to the world, still to prevail the on-time issues. The study commenced with the identification of back-locks affecting the lead time in the apparel industry. A three step strategy is proposed through this study to ensure a shorter lead time.